Fe2O3–TiO2 nanosystems by a hybrid PE-CVD/ALD approach: controllable synthesis, growth mechanism, and photocatalytic properties1. Issue 32 (28th August 2015) - Barreca, Davide; Carraro, Giorgio; Warwick, Michael E. A.; Kaunisto, Kimmo; Gasparotto, Alberto; Gombac, Valentina; Sada, Cinzia; Turner, Stuart; Van Tendeloo, Gustaaf; Maccato, Chiara; Fornasiero, Paolo
<x xml:space="preserve">Abstract</x> High purity Fe2O3–TiO2 nanocomposites are successfully used in the photocatalytic degradation of aqueous pollutants triggered by solar/visible light.